The Role of G Protein-Coupled Receptors (GPCRs) and Calcium Signaling in Schizophrenia. Focus on GPCRs Activated by Neurotransmitters and Chemokines - Tomasz Boczek; Joanna Mackiewicz; Marta Sobolczyk; Julia Wawrzyniak; Malwina Lisek; Bozena Ferenc; Feng Guo; Ludmila Zylinska (Cells, 2021)
Schizophrenia is a common debilitating disease characterized by continuous or relapsing episodes of psychosis. Although the molecular mechanisms underlying this psychiatric illness remain incompletely understood, a growing body of clinical, pharmacological, and genetic evidence suggests that G protein-coupled receptors (GPCRs) play a critical role in disease development, progression, and treatment. This pivotal role is further highlighted by the fact that GPCRs are the most common targets for antipsychotic drugs. The GPCRs activation evokes slow synaptic transmission through several downstream pathways, many of them engaging intracellular Ca2+ mobilization. Dysfunctions of the neurotransmitter systems involving the action of GPCRs in the frontal and limbic-related regions are likely to underly the complex picture that includes the whole spectrum of positive and negative schizophrenia symptoms. Therefore, the progress in our understanding of GPCRs function in the control of brain cognitive functions is expected to open new avenues for selective drug development. In this paper, we review and synthesize the recent data regarding the contribution of neurotransmitter-GPCRs signaling to schizophrenia symptomology.